MENANAMKAN NILAI KARAKTER MELALUI DONGENG: ANALISIS BUKU 'BAHASA INDONESIA UNTUK SD DAN MI KELAS III' - Mukhlisin, Dede; Leni Malinda; Hariati, Emy (REKOGNISI : Jurnal Pendidikan dan Kependidikan (E-ISSN 2599-2260), 2024)
This study aims to describe the character values found in the fables of the book "Bahasa Indonesia untuk SD dan MI Kelas III" at SDN 100311 Palsabolas. The research employed a descriptive method with a case study design, involving an analysis of the book and interviews with the third-grade homeroom teacher as data sources. Data collection techniques included observation, interviews, and document analysis. The findings revealed various character values in the fables, such as religiosity (5.56%), honesty (5.56%), hard work (16.67%), independence (5.56%), curiosity (16.67%), appreciation of achievements (11.11%), and responsibility (5.56%). The fable "Keong Emas" contains six character values, making it the story with the most character values, while "Pak Belalang" and "Batu Menangis" each contain three character values. Overall, 12 character values were identified, providing a foundation for character education for students. This study suggests that teachers and parents use fables as an alternative medium for teaching character values, students select positive values to apply in their daily lives, and textbook authors incorporate additional character values that are not yet included to enrich the educational content in fables.